2+{4+[7*(6:2-5)+3]:2}:1
Răspunsuri la întrebare
Răspuns de
0
2 + { 4 + [ 7 × ( 6 ÷ 2 - 5 ) + 3 ] ÷ 2 } ÷ 1 = - 3
Deoarece :
• 6 ÷ 2 = 3
• 2 - 5 = - 3
• 7 × ( - 3 ) = - 21
• -21 + 3 = - 18
• - 18 ÷ 2 = - 9
• 4 + - 9 = - 5
• - 5 ÷ 1 = - 5
• 2 + ( - 5 ) = - 3
Deoarece :
• 6 ÷ 2 = 3
• 2 - 5 = - 3
• 7 × ( - 3 ) = - 21
• -21 + 3 = - 18
• - 18 ÷ 2 = - 9
• 4 + - 9 = - 5
• - 5 ÷ 1 = - 5
• 2 + ( - 5 ) = - 3
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă